2004
DOI: 10.1017/s1049023x00001667
|View full text |Cite
|
Sign up to set email alerts
|

Counting Crises: US Hospital Evacuations, 1971–1999

Abstract: Objectives:To investigate the relative distribution of hazards causing hospital evacuations, thereby to provide rudimentary risk information for hospital disaster planning.Methods:Cases of hospital evacuations were retrieved from newspaper and publication databases and classified according to hazard type, proximate and original cause, duration, and casualties. Both partial and full evacuations were included. The total number of evacuation incidents for all hazards were compared to the total number of hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
79
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 4 publications
2
79
0
Order By: Relevance
“…As per the findings of the present study, the greatest risk was related to earthquake and dust, which is consistent with the results of Sokhanvar et al [17]. Sternberg et al [18], after reviewing 275 reports on natural disasters during 1971-1999, found that earthquake was the fifth highest form of disaster in terms of repeatability. In relationship with the degree of readiness of the studied centers in facing the crisis and maneuvers conducted, it was found that maneuvers are well performed.…”
Section: Discussionsupporting
confidence: 93%
“…As per the findings of the present study, the greatest risk was related to earthquake and dust, which is consistent with the results of Sokhanvar et al [17]. Sternberg et al [18], after reviewing 275 reports on natural disasters during 1971-1999, found that earthquake was the fifth highest form of disaster in terms of repeatability. In relationship with the degree of readiness of the studied centers in facing the crisis and maneuvers conducted, it was found that maneuvers are well performed.…”
Section: Discussionsupporting
confidence: 93%
“…1 Between 1950 and 2005, 286 hospital evacuations have been described, including horizontal evacuation (within the same floor), vertical evacuation (between floors), evacuation of a ward or wing, and complete hospital evacuation. [4][5][6][7][8][9][10] Of the 286 between 1971 and 1999, 275 were reviewed by Sternberg et al 8 There are 22 reported cases of complete hospital evacuation since 1950; of these, 1 occurred in Canada and 8 resulted from the 1994 Northridge, California, earthquake. 4,5,[7][8][9][10][11][12][13][14][15][16][17][18] Of 43 reported incidents for which duration is known, only 12 evacuations lasted longer than 24 hours.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Of the 286 between 1971 and 1999, 275 were reviewed by Sternberg et al 8 There are 22 reported cases of complete hospital evacuation since 1950; of these, 1 occurred in Canada and 8 resulted from the 1994 Northridge, California, earthquake. 4,5,[7][8][9][10][11][12][13][14][15][16][17][18] Of 43 reported incidents for which duration is known, only 12 evacuations lasted longer than 24 hours. 8 Eleven percent of evacuations in the series reviewed by Sternberg et al listed at least 1 casualty, and the deadliest reported hospital disaster occurred in 1971, when partial collapse of a California Veteran's Administration hospital claimed 49 lives.…”
mentioning
confidence: 99%
See 2 more Smart Citations